Colonization of root endophytic fungus Serendipita indica improves drought tolerance of Pinus taeda seedlings by regulating metabolome and proteome - Wu, Chu; Yang, Yujie; Wang, Yun; Zhang, Wenying; Sun, Honggang (Frontiers in Microbiology, 2024)
Pinus taeda is an important forest tree species for plantations because of its rapid growth and high yield of oleoresins. Although P. taeda plantations distributes in warm and wet southern China, drought, sometime serious and long time, often occurs in the region. In order to explore drought tolerance of P. taeda and usage of beneficial microorganisms, P. taeda seedlings were planted in pots and were inoculated with root endophytic fungus Serendipita indica, and finally were treated with drought stress for 53 d. Metabolome and proteome of their needles were analyzed. Results showed that S. indica inoculation of P. taeda seedlings under drought stress caused great changes in levels of some metabolites in their needles, especially some flavonoids and organic acids. Among them, levels of eriocitrin, trans-aconitic acid, vitamin C, uric acid, alpha-ketoglutaric acid, vitamin A, stachydrine, coumalic acid, itaconic acid, calceolarioside B, 2-oxoglutaric acid, and citric acid were up-regulated more than 3 times in inoculated seedlings under drought stress, compared those of non-inoculated seedlings under drought stress. KEGG analysis showed that some pathways enriched in inoculated seedlings under drought stress, such as flavonoid biosynthesis, ascorbate and aldarate metabolism, C5-branched dibasic acid metabolism. Proteome analysis revealed some specific differential proteins. Two proteins, H9X056 and H9VDW5, only appeared in the needles of inoculated seedlings under drought stress. The protein H9VNE7 was up-regulated more than 11.0 times as that of non-inoculated seedlings under drought stress. In addition S. indica inoculation increased enrichment of water deficient-inducible proteins (such as LP3-1, LP3-2, LP3-3, and dehydrins) and those involved in ribosomal structures (such as A0A385JF23). Meanwhile, under drought stress the inoculation caused great changes in biosynthesis and metabolism pathways, mainly including phenylpropanoid biosynthesis, cutin, suberine and wax biosynthesis, and 2-oxocarboxylic acid metabolism. In addition, there were positive relationships between accumulation of some metabolites and enrichment of proteins in P. taeda under drought stress. All together, our results showed great changes in metabolome and proteome in inoculated seedlings under drought stress and provided a guideline to further study functions of metabolites and proteins, especially those related to drought stress.